Reunion : finding the disappeared children of El Salvador - Barnert, Elizabeth, 1979- (University of California Press, 2023)
"This captivating ethnography reveals the immediate and persisting impact of forced family separations and the eventual reunifications in communities affected by El Salvador's civil war. In 2005, medical student Elizabeth Barnert traveled to El Salvador to build a DNA bank for reuniting families forcibly separated during the Salvadoran civil war. Based on fifteen years of interviews and field notes, Reunion chronicles families' experiences with military attacks, child disappearances, and family separations, the joy of reunion and the arduous process of reintegration. Barnert works alongside Jesuit priest and Pro-Búsqueda founder Father Jon Cortina, former rebel fighters, and reformed gang members. She meets an eight-year-old journeying north to reunite with her mother and a young woman returning to El Salvador twenty years after her adoption abroad. Reunion includes a foreword by renowned anthropologist Philippe Bourgois, along with his firsthand account of fleeing a Salvadoran military raid, and never-before-published photos and children's drawings from the war. Told through the voices of activists and survivors, this groundbreaking ethnography illuminates the cycles of poverty and violence driving immigration and ongoing separations around the world"-- Provided by publisher.
Keywords: Family reunification -- El Salvador -- 21st century.; Disappeared persons -- El Salvador.; Children -- El Salvador.; Civil war -- Social aspects -- El Salvador.; Regroupement familial -- Salvador -- 21e siècle.; Personnes disparues -- Salvador.; Guerre civile -- Aspect social -- Salvador.; Enfance -- Salvador.; POLITICAL SCIENCE / Human Rights; Children; Disappeared persons; Family reunification; El Salvador; 2000-2099; aid.; america.; central.; children.; civil war.; cultural.; culture.; diplomacy.; disappear.; el salvador.; ethnography.; familial.; family.; force.; immigration.; kidnapped.; military.; missing.; political figures.; poverty.; rebel.; rebelion.; reunification.; reunion.; salvadorian.; stolen.; trafficking.; violence.; youth.; Electronic books.